2020
DOI: 10.3390/nu12010132
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Probiotics: A Systematic Review

Abstract: Probiotic is little known for its benefits on upper gastrointestinal health. The objective of this systematic review was to examine the efficacy of probiotics in alleviating the frequency and severity of symptoms in gastroesophageal reflux disease (GERD) in the general adult population. The PubMed and Web of Science databases were searched for prospective studies on GERD, heartburn, regurgitation, and dyspepsia, without any limitation on sample size. The Jadad scale was used to evaluate the quality of randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 40 publications
(98 reference statements)
1
36
0
6
Order By: Relevance
“…Traditionally, probiotics was thought bene cial to prevent gastrointestinal disorders such as acute gastroenteritis, antibiotic-associated diarrhoea, or necrotising enterocolitis (28). However, no broad consensus exists to recommend the use of probiotics in the prevention of GER.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, probiotics was thought bene cial to prevent gastrointestinal disorders such as acute gastroenteritis, antibiotic-associated diarrhoea, or necrotising enterocolitis (28). However, no broad consensus exists to recommend the use of probiotics in the prevention of GER.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, probiotics were thought to prevent gastrointestinal disorders, such as acute gastroenteritis, antibiotic-associated diarrhea, or necrotizing enterocolitis (28). However, no broad consensus exists to recommend the use of probiotics in the prevention of GER.…”
Section: Discussionmentioning
confidence: 99%
“…Daily supplementation of maltosyl-isomaltooligosaccharides as a prebiotic for lactobacilli led to a significant improvement of symptoms in patients with chronic GERD [ 124 ]. A systematic review suggested probiotics led to a similar improvement in GERD symptoms [ 125 ]. However, it has been noted that studies with improved internal validity are warranted to confirm the efficacy of probiotics in GERD [ 125 ].…”
Section: Therapeutic Potential Of Esophageal Microbiotamentioning
confidence: 99%